Most prevalent jobs of young college and CEGEP certificate and diploma graduates by detailed field of study - Tomasz Handler; Marc Frenette (Economic and Social Reports)
One of the main investments individuals can make throughout their lives is the decision to pursue a postsecondary education. The purpose of this article is to present results from the 2021 Census of Population on the most prevalent occupations held by graduates of various college and CEGEP certificate and diploma programs who were aged 25 to 34.